The accuracy of bone mapping and guided flapless implant placement using a novel surgical guide : a human cadaver study - Fitzgerald, Maurice Edward (Trinity College (Dublin, Ireland). School of Dental Science, 2009)
Dental Implants are a predictable way of replacing missing teeth. However in some instances the position of the implant is a hindrance to providing a functional and aesthetic restoration. The problems associated with sub-optimal implant placement are numerous and include biomechanical, aesthetic, economic, and functional issues in addition to iatrogenic damage. Many techniques have been developed to help optimise the positioning of dental implants. Most use the restorative driven approach where the final result is visualised and the implant placed according to the restorative parameters. Guided surgery such as CT based stereolithographic guides have been developed to aid in precise implant placement and these have proven reliable and accurate. In some less complex cases however the radiation dose and expense of such systems may not be justified. The model based NobelGuide ™ uses bone mapping data to visualise the bone morphology and implant placement takes place on a stone cast from which a stent is fabricated to facilitate accurate spatial placement of the implant. This technique may have advantages in terms of reduced radiation dose, expense and simplicity over the CT based systems. The accuracy of this technique however is unknown. The aims of the current study were to measure the accuracy of the model based NobelGuide ™ and evaluate if the bone mapping data are sufficient for implant placement.
Keywords: Dental Surgery, D.Ch.Dent.; Ph.D. Trinity College Dublin